2008
DOI: 10.1016/j.fct.2008.01.026
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition, and antioxidant and antimicrobial activities of three hazelnut (Corylus avellana L.) cultivars

Abstract: Hazelnut (Corylus avellana L.) is a very popular dry fruit in the world being consumed in different form and presentations. In the present work, three hazelnut cultivars (cv. Daviana, Fertille de Coutard and M. Bollwiller) produced in Portugal, were characterized in respect to their chemical composition, antioxidant potential and antimicrobial activity. The samples were analysed for proximate constituents (moisture, fat, crude protein, ash), nutritional value and fatty acids profile by GC/FID. Antioxidant pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
114
1
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(126 citation statements)
references
References 27 publications
8
114
1
3
Order By: Relevance
“…The main compounds identified belong to four groups: flavan-3-ols (catechin, epicatechin, two procyanidin dimers and three procyanidin trimers); flavonols (myricetin-3-Orhamnoside, quercetin pentoside and quercetin-3-Orhamnoside); benzoic acids (gallic acid and protocatechuic acid); and dihydrochalcones (phloridzin). These results contribute to biochemical characterization and explain genetic variability within the European hazelnut resources, as reported by different authors (Garrone and Vacchetti 1994;Durak et al 1999;Alasalvar et al 2009;Kornsteiner et al 2006;Oliveira et al 2008;Arcan and Yemenicioglu 2009;Bacchetta et al 2011). The large variation in phenolic content among cultivars indicates different antioxidant and nutritional values for their nuts, which is of great interest to consumers and industrial users (Jakopic et al 2010).…”
Section: Biochemical Characterization Of Hazelnut Germplasmsupporting
confidence: 48%
See 1 more Smart Citation
“…The main compounds identified belong to four groups: flavan-3-ols (catechin, epicatechin, two procyanidin dimers and three procyanidin trimers); flavonols (myricetin-3-Orhamnoside, quercetin pentoside and quercetin-3-Orhamnoside); benzoic acids (gallic acid and protocatechuic acid); and dihydrochalcones (phloridzin). These results contribute to biochemical characterization and explain genetic variability within the European hazelnut resources, as reported by different authors (Garrone and Vacchetti 1994;Durak et al 1999;Alasalvar et al 2009;Kornsteiner et al 2006;Oliveira et al 2008;Arcan and Yemenicioglu 2009;Bacchetta et al 2011). The large variation in phenolic content among cultivars indicates different antioxidant and nutritional values for their nuts, which is of great interest to consumers and industrial users (Jakopic et al 2010).…”
Section: Biochemical Characterization Of Hazelnut Germplasmsupporting
confidence: 48%
“…Among dry fruits, hazelnuts show an intermediate total polyphenols content, from a major content in walnuts and pistachios to a lesser value in pine nuts and macadamia nuts (Delgrado et al 2010). Moreover, hazelnut skin could potentially be considered as an inexpensive source of natural antioxidants (Alasalvar et al 2009) and leaf extract also exhibited high antioxidant activity (Oliveira et al 2008).…”
Section: Biochemical Characterization Of Hazelnut Germplasmmentioning
confidence: 99%
“…β-Carotene-Linoleic acid system model: Antioxidant capacity of the extracts can also be measured by β-carotene-linoleic acid system model [11]. Firstly the β-carotene solution was prepared.…”
Section: Methodsmentioning
confidence: 99%
“…Proximate composition of hazelnut is about 62 % fat, 16 % protein and 11 % carbohydrate and changes with variety. Hazelnut composition (Alasalvar et al 2003;Venkatachalam and Sathe 2006), and good antioxidant effects of hazelnut (Amaral et al 2006;Oliveira et al 2008) are reported in literature.…”
Section: Introductionmentioning
confidence: 99%